Removal of accidentally ingested large foreign object via the anus after watchful waiting (Indian Journal of Case Reports, 2019)
One of the commonest complaints, for which a patient arrives in hospitals, is the presence of foreign body. It could be due to accidental ingestion or any other cause which leads to presences of a foreign body in the gastrointestinal tract. It is believed that foreign objects larger than 5–6 cm in size are unlikely to pass through the duodenum. Here, we describe a case wherein the patient accidentally swallowed a 7-cm-sized mouthguard that could not be removed by emergency upper gastrointestinal endoscopy but was subsequently removed via the anus after a period of watchful waiting.